FINANSIAL FEASIBILITY ANALYSIS OF ARABICA COFFEE FARMING IN MANIKLIYU VILLAGE, KINTAMANI DISTRICT, BALI - Luh Anggreni Dewi; Ni Nyoman Alit Purnami (International Conference on Multidisciplinary Research Perspective, 2025)
This study analyzes the financial feasibility and development prospects of Arabica coffee farming in Manikliyu Village, Kintamani District, Bangli Regency, Bali Province. Arabica coffee represents one of the key highland commodities contributing significantly to the regional economy and rural livelihoods, particularly within the Kintamani Bali Coffee Geographical Indication (GI) area. The research aims to evaluate whether Arabica coffee farming is economically viable and to assess its potential for sustainable agribusiness development. Financial feasibility was analyzed using four standard indicators: Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C), and Payback Period (PP). Primary data were collected through structured interviews and surveys with 40 Arabica coffee farmers, while secondary data were obtained from relevant government agencies, cooperatives, and academic references.The results reveal that Arabica coffee farming in the study area is financially feasible and profitable. The NPV value of IDR 45,860,000 per hectare indicates that the present value of benefits exceeds production costs over the economic life of the coffee plants. The IRR of 18.75% surpasses the prevailing commercial interest rate of 10–12% per year, suggesting that the investment generates attractive returns. The B/C ratio of 1.72 confirms economic efficiency, as every IDR 1.00 invested yields IDR 1.72 in benefits. Moreover, the Payback Period of 3.2 years shows that the initial capital investment can be recovered relatively quickly compared to the 10–15-year productive lifespan of Arabica coffee.Overall, the findings indicate that Arabica coffee farming in Manikliyu Village is not only financially viable but also has strong potential as a regional flagship commodity. To ensure sustainability, continuous efforts are required to strengthen farmer institutions, enhance production efficiency, and expand access to financing and premium markets.